Screening of Potential Inhibitors Targeting the Main Protease Structure of SARS-CoV-2 via Molecular Docking, and Approach with Molecular Dynamics, RMSD, RMSF, H-Bond, SASA and MMGBSA - da Fonseca, Aluísio Marques; Caluaco, Bernardino Joaquim; Madureira, Junilson Martinho Canjanja; Cabongo, Sadrack Queque; Gaieta, Eduardo Menezes; Djata, Faustino; Colares, Regilany Paulo; Neto, Moises Maia; Fernandes, Carla Freire Celedonio; Marinho, Gabrielle Silva; dos Santos, Hélcio Silva; Marinho, Emmanuel Silva (Molecular biotechnology, 2024)
Severe Acute Respiratory Syndrome caused by a coronavirus is a recent viral infection. There is no scientific evidence or clinical trials to indicate that possible therapies have demonstrated results in suspected or confirmed patients. This work aims to perform a virtual screening of 1430 ligands through molecular docking and to evaluate the possible inhibitory capacity of these drugs about the M pro protease of Covid-19. The selected drugs were registered with the FDA and available in the virtual drug library, widely used by the population. The simulation was performed using the MolAiCalD algorithm, with a Lamarckian genetic model (GA) combined with energy estimation based on rigid and flexible conformation grids. In addition, molecular dynamics studies were also performed to verify the stability of the receptor-ligand complexes formed through analyses of RMSD, RMSF, H–Bond, SASA, and MMGBSA. Compared to the binding energy of the synthetic redocking coupling (−6.8 kcal/mol/RMSD of 1.34 Å), which was considerably higher, it was then decided to analyze the parameters of only three ligands: ergotamine (−9.9 kcal/mol/RMSD of 2.0 Å), dihydroergotamine (−9.8 kcal/mol/RMSD of 1.46 Å) and olysio (−9.5 kcal/mol/RMSD of 1.5 Å). It can be stated that ergotamine showed the best interactions with the M pro protease of Covid-19 in the in silico study, showing itself as a promising candidate for treating Covid-19.